Y-STR data, Y-SNP data and geographic location of brown bears in Northern Europe - Schregel, Julia; Eiken, Hans Geir; Grøndahl, Finn Audun; Hailer, Frank; Aspi, Jouni; Kojola, Ilpo; Tirronen, Konstantin; Danilov, Pjotr; Rykov, Alexander; Poroshin, Eugene; Janke, Axel; Swenson, Jon E.; et al. (Dryad Digital Repository, 2015)
This data file contains sample names (indicating the sampling location used to group samples for the analyses) and the respective Y-STR and Y-SNP haplotypic profile for each individual as well as the assigned Y chromosomal haplotype. In addition, each sample is given the samling country and the sampling coordinates in decimal format.